Building the Competitive Advantage MSMEs in the Digital Era: The Role of Digital Ecosystem and Pentahelix Synergy - Mulyaningtyas, Mulyaningtyas; Wardana, Ditya (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
This study investigates not only the impact of the digital ecosystem and pentahelix synergy on Malang City MSMEs' income, but also how it affects their sustainability. The study's purpose is to investigate the impact of pentahelix synergy and the digital ecosystem on competitive advantage, which is moderated by sales growth. 74 MSMEs were randomly selected as samples for the descriptive quantitative research, which focuses on MSMEs in Malang City that are more than five years old. The data was obtained via a questionnaire, and the assessment weight was established using a linkert scale. Data analysis employs validity tests, normality tests, and moderating variable regression. The findings revealed that the digital ecosystem and the three pentahelix characteristics, which are influenced by sales growth, had no discernible impact on MSMEs' competitiveness. The originality of study in which pentahelix synergy also engages the digital ecosystem in establishing MSMEs' competitive advantage, implies that MSMEs and pentahelix elements should understand the relevance of incorporating the digital ecosystem in achieving competitive advantage.